Relações familiares simultâneas à luz da ordem civil constitucional - Ribeiro, Bruno Marques (2013)
This paper aims to point out an understanding about the simultaneous families phenomenon in contemporary Brazilian Law. The family, once a specific form of human aggregation which assures the survival of its members, changed throughout life cycles, cultural contexts and interpersonal conflicts and it has still gone through transformations that corresponded to changes in the society. Family thus figures as a changeable entity, since it has been modifying and organizing itself, and that s why is difficult to identify family as an unique or ideal model. In the classical system established by the Brazilian Civil Codification of 1916, the familiar model was designed from an institutional perspective of family, with a patriarchal and hierarchical character. Thus, the protection of the familiar entity was solely centered on the matrimony. Traditional Brazilian Civil Law is absorbing renovations with the purpose of readapt its usage to the contemporary facts and to the new social phenomenon, aiming the resolution of the irregularities and conflicts, especially in the family relationships field. Brazilian Federal Constitution of 1988, which was a milestone in the recognition of changes in Brazilian Family Law, acknowledged the pluralism in the formation of families and also the new conception of family. Families are thus entities considered egalitarian, decentralized, democratic and mainly based on bonds of affection. However, the family models referred to in Brazilian legal system are still not enough to attend the social demand of the dynamism of human relations. In this context, this study focuses on the concept of plural families in modern family life, in which polygamous families are embedded, with the goal to demonstrate that a systematic interpretation of the Brazilian legal system, notably in the terms and principles of the Constitutional Civil Order, points out the acknowledgment and attribution of legal effect to these family entities still so discriminated.